Effects of Pollination Technique on Agronomic and Physicochemical Characteristics of Date Palm (Phoenix dactylifera L.) Fruits in the Sudan Savannah Region of Nigeria - Mustapha Sunusi; Muhammad Sani Isiyaku; Jamilu Halidu; Danmaigoro Olanrewaju (Department of Agronomy and Horticulture, IPB University, 2026)
Pollination is critical for producing many crops, and both insect- and wind-based pollination systems are increasingly disrupted by bloom asynchrony, weather events, and the high demand for available insect pollinators. Artificial pollination systems can provide yield security even in poor pollination scenarios and have attracted attention over the past decade. In Nigeria, date farmers still practice the oldest and most traditional technique of pollination, where male spikelets are manually inserted into the female inflorescence. This ancestral practice has many setbacks, which led to searching for other means for improving date yield. The present study aims to compare the agronomic and biochemical characteristics of the date ‘Danshuwarin’ cultivar under different pollination methods. Three methods were tested: traditional pollination, pollen dusting, and pollen suspension. The results obtained showed the dusting technique to be the most effective and efficient, followed by conventional methods. In contrast, pollen suspension has the highest number of fruit sets (80.79%) and retention rate (67.42%), while yield is 5.3% with the lowest parthenocarpic fruits of <2%. The results provide baseline information to uncover different pollination techniques on other Nigerian date palm varieties grown in diverse agroecological zones.